PWE-098 Clostridium difficile diarrhoea—the changing hospital epidemiology and clinical outcomes from a high prevalence area in North East England. (28th May 2012) - Ross, J; Brown, P; Aldridge, C; Lim, L; Nayar, D; Sloss, J; Allison, D; Dhar, A
Abstract : Introduction: Clostridium difficile associated diarrhoea (CDAD) is an important hospital acquired infection. In 2008–2009 Co. Durham had one of the highest reported annual incidence of CDAD with 232 cases, 74.4 cases/100 000 bed days. Following strict antibiotic stewardship in 2009, we set out to examine the changes to the hospital based epidemiology of CDAD in our three hospitals over a 12-month period. Methods: Between June 2010 and May 2011, 70 patients with positive stool C difficile toxin were identified from the Microbiology database, and 56 case notes reviewed. Patient demographics, clinical symptoms, risk factors, severity, treatment for CDAD, and multi-disciplinary team decisions were recorded. Clinical outcomes including length of stay, treatment, mortality, and relapses were analysed and compared to standard hospital episode statistics (HES). Results: The annualised hospital incidence of CDAD was 70/20 000 admissions, age range 2–100 yrs (mean 75.5, M: F). 76.8% patients were older than 70 yrs. 43% had received antibiotics prior to admission and 35 (62%) patients were commenced on antibiotics in hospital. The top 5 were Amoxicillin, Co-amoxiclav, Flucloxacillin, Cephalexin and Trimethoprim. 62% of these had received one course of antibiotic, and 30% two or more courses. 39% patients had a previous admission to hospital in the preceding 12 weeks, 46.4% were taking a PPI and 35.7% a laxative. C difficile was confirmed by both toxin and GDH positivity in 80.4%, and by toxin positivity only in 19.6%. Total length of stay ranged from 51 days (16%). A positive diagnosis was made in 80% patients, but severity was not always recorded. Stool charts were completed in 70%, serum lactate checked in 10% and abdominal x-ray done in 30%. Only 25% patients were seen by an MDT member. 78.5% pts were treated, 30/44 (68%) with Metronidazole and 11/44 (25%) with Vancomycin as first line drugs. 3/44 patients received both drugs initially. 30.4% pts received ≤ 7 days, 50% upto 14 days and 19.6% ≥ 14 days treatment. All cause mortality was 25%, almost entirely in the elderly. 7% had a recurrence, all treated by Vancomycin and pulsed/tapered regimes and probiotics were used infrequently. Conclusion: CDAD continues to be an important hospital acquired infection with a significant increase in hospital length of stay and high mortality rates, especially in the elderly. This study indicates that a significant proportion of CDAD may be acquired in the community. Adherence to national recommendations for management and involvement of the MDT needs to be encouraged to improve outcomes. Competing interests: None declared.